Credit supply and the rise in college tuition: Evidence from the expansion in federal student aid programs - David O. Lucca; Taylor Nadauld; Karen Shen (Federal Reserve Bank of New York, 2015)
When students fund their education through loans, changes in student borrowing and tuition are interlinked. Higher tuition costs raise loan demand, but loan supply also affects equilibrium tuition costs - for example, by relaxing students' funding constraints. To resolve this simultaneity problem, we exploit detailed student-level financial data and changes in federal student aid programs to identify the impact of increased student loan funding on tuition. We find that institutions more exposed to changes in the subsidized federal loan program increased their tuition disproportionately around these policy changes, with a sizable pass-through effect on tuition of about 65 percent. We also find that Pell Grant aid and the unsubsidized federal loan program have pass-through effects on tuition, although these are economically and statistically not as strong. The subsidized loan effect on tuition is most pronounced for expensive, private institutions that are somewhat, but not among the most, selective.
Keywords: G28; I22; 330; student loans; college tuition